The secret life of Walter Mitty [videorecording (DVD)] - Stiller, Ben, 1965-; Wiig, Kristen, 1973-; MacLaine, Shirley, 1934-; Scott, Adam, 1973-; Hahn, Kathryn, 1974-; Penn, Sean, 1960-; Thurber, James, 1894-1961
Watch the classic story by James Thurber, about a daydreamer who escapes his anonymous life by disappearing into a world of fantasies filled with heroism, romance, and action. When his job along with that of his co-worker are threatened, Walter takes action in the real world embarking on a global journey that turns into an adventure more extraordinary than anything he could have ever imagined.